(untitled) (Terr@ Plural, 2020)
Soil can be considered an element of geodiversity with different values; however, its significance is often underestimated. In this perspective, this research aims to apply to the soils the geodiversity valuation system based on ecosystem support, provision, regulation, cultural and knowledge services, developed by Gray (2013). The research was conducted at the PROMATA Farm, in the river Escuro drainage basin, Ubatuba Municipality, São Paulo State. Results of physical and chemical analyzes refer to the good soil structure, soil density average less than 0.8 g/cm³, and the total porosity average over 70%, it is an important condition for the soil to perform its functions. Therefore, soils perform several ecosystem services, essential for the accomplishment of human activities and the balanced operation of the environmental systems.